Ocular Aberrations and Retinal Thickness Variations After Moderate-Term Reading on Electronic Devices by Age - María Arcas-Carbonell; Elvira Orduna-Hospital; María Mechó-García; María Munarriz-Escribano; Ana Sanchez-Cano (Photonics)
Background: This study aims to evaluate subjective visual fatigue and objective optical and morphological changes in ocular structures after intermediate-duration reading on an iPad and an Ebook across different age groups. Methods: The sample included 108 right eyes from healthy subjects aged 18 to 66 years. The participants read for 20 min on an Ebook and another 20 min on an iPad under controlled illumination conditions. Aberrometry and retinal optical coherence tomography (OCT) measurements were taken before and after each reading session. Parameters such as total aberration, high-order aberration (HOA), low-order aberration (LOA), and retinal thickness in the nine Early Treatment Diabetic Retinopathy Study (ETDRS) areas were measured. The sample was analyzed as a whole and divided into five age groups by decade. Results: This study included 66 women (61.11%) and 42 men (38.89%), with an average age of 36.58 years (±14.83). The aberrometry results revealed significant differences in the total root mean square (RMSTOTAL) after reading on both devices (p = 0.001). Low-order aberrations (RMSLOA) also changed significantly (p = 0.001 for Ebook, p = 0.002 for the iPad), but high-order aberrations (RMSHOA) did not. Central retinal thickness increased significantly after reading on the Ebook (p < 0.001) but not on the iPad. The peripheral retinal thickness did not change significantly. Conclusion: Moderate-duration reading increases LOA and central retinal thickness, with variations by age group and more pronounced effects from the Ebook, whereas HOA remains unaffected.